2008
DOI: 10.1088/0964-1726/17/4/045007
|View full text |Cite
|
Sign up to set email alerts
|

The glass transition temperature of polyurethane shape memory polymer reinforced with treated/non-treated attapulgite (playgorskite) clay in dry and wet conditions

Abstract: Attapulgite (playgorskite), a kind of nanosized fibrous clay mineral, may provide a simple and cheap alternative to improve the stiffness and actuation stress of shape memory polymers (SMPs). As a first step, in this paper, we investigate the glass transition temperature of a polyurethane SMP reinforced with treated/non-treated attapulgite in wet and dry conditions. In addition to confirming the strong influence of moisture, the results reveal that non-treated clay significantly reduces the glass transition te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…[4,7,9,10,25,37,43,139,148,149], based on the principles of the above discussed working mechanisms, the performance of existing materials can be optimized by means of controlling the processing parameters in programming [113,126,150]. Figure 30 illustrates the influence of the programming temperature on shape fixity ratio (R f ) and shape recovery ratio (R r ).…”
Section: Optimizationmentioning
confidence: 99%
“…[4,7,9,10,25,37,43,139,148,149], based on the principles of the above discussed working mechanisms, the performance of existing materials can be optimized by means of controlling the processing parameters in programming [113,126,150]. Figure 30 illustrates the influence of the programming temperature on shape fixity ratio (R f ) and shape recovery ratio (R r ).…”
Section: Optimizationmentioning
confidence: 99%
“…We demonstrate the advantages of utilizing this polymer for novel applications, which are difficult to be realized by other materials. By mixing the polyurethane SMP with, for instance, attapulgite clay [20], we can improve the strength of the polymer and increase the water absorption speed. Hence, fast reaction and high actuation stress can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The attapulgite clay was heat-treated in an furnace (in air) at 850 °C for 2 hours [20,21], and then held in an oven at 100 °C for 12 hours. High resolution transmission electron microscopy (HR-TEM, JEOL 2010F) showed that the treated nano-clay formed a three-dimensional bundled network structure in which the length of single clay fibre varied from sub-micrometer to a few micrometers and the diameter was in the order tens of nanometres (see Figure 1(a)).…”
Section: Methodsmentioning
confidence: 99%
“…The ring-like scattered diffraction spots reveal the nanocrystalline feature of the treated fibres as shown by the inset electron diffraction pattern in Figure 1(a). The corresponding HR-TEM images in Figure 1 A Haake Rheocord 90 Torque Mixer was used for the mechanical mixing of the PU and attapulgite clay at 200 °C and the SMP nanocomposite sheets (about 3 mm thickness, with nanoclay contents of 10, 20 and 30 wt.%) were prepared by a hot-pressing method [21]. TEM was used to study the microstructure of the nanocomposites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation